Bearing Capacity of Hollow GFRP Pipe-Concrete-High Strength Steel Tube Composite Long Columns Under Eccentrical Compression Load - Ji, Jing; Zeng, Wen; Wang, Ruili; Ren, Hongguo; Zhang, Lei; Liu, Yuchen; Jiang, Liangqin; He, Lingjie; Lin, Yubo; Yu, Chenyu (Frontiers in Materials, 2021)
To investigate the bearing capacity of the hollow Glass Fiber Reinforced Polymer (GFRP) pipe-concrete-steel tube composite long columns subjected to eccentrical compression load, 33 hollow GFRP pipe-concrete-steel tube composite long columns have been designed. The slenderness ratio (λ), compressive strength of concrete cube (fcu), eccentricity (e) and so on are the main parameters. Based on constitutive models for steel, GFRP and confined concrete, numerical simulation of the hollow GFRP pipe-concrete-high strength steel tube composite long columns has been carried out by using software ABAQUS. The rationality of the constitutive models and modeling method has been verified by comparing the experimental and simulated load-displacement curves. The influence of different parameters on the mechanical behavior of this kind of column has been investigated. Results show that with the increasing of t1, t2 and fcu, the ultimate eccentrical compression bearing capacity of the specimen increases. With the increasing of e, the ultimate displacement of the specimens increases, while the ultimate eccentrical compression bearing capacity decreases. The eccentricity has a significant influence on the ultimate eccentrical compression bearing capacity. With the increasing of λ, the ultimate eccentrical compression bearing capacity of the specimens gradually decreases. The specimens suffer from ductile failure. The formula of the ultimate eccentrical compression bearing capacity of the composite columns is obtained by statistical regression. The study can provide theoretical support for the application of the composite columns in practical engineering.